Gonococcal urethritis caused by a multidrug resistant Neisseria gonorrhoeae strain with high-level resistance to spectinomycin in China - Shao-Chun Chen; Li-Hua Hu; Xiao-Yu Zhu; Yue-Ping Yin (Emerging Microbes and Infections, 2020)
ABSTRACTWe report a recent (2018) gonorrhoeal urethritis caused by a multidrug-resistant Neisseria gonorrhoeae strain in China. The isolated N. gonorrhoeae strain from a male and female pair expressed high-level resistance to spectinomycin (SPC), azithromycin, and other antibiotics but was sensitive to ceftriaxone. The SPC high-level resistance (MIC = 2048 mg/L) was due to a small deletion in rspE that caused two amino acid changes in ribosomal protein S5.